Occurrence of Pathogenic Fungi in Soil from Pre-Primary School Playgrounds in Birnin Kebbi - Gulumbe, B. H.; Aliyu, B.; Abubakar, B.; Sambo, K. H.; Muhammad, W. N.; Usman, N. I. (UMYU Journal of Microbiology Research)
A study was conducted to determine the predominant pathogenic fungi from 5 selected pre - primary school playgrounds. The five (5) schools considered for this study were identified as PPSA, PPSB, PPSC, PPSD, and PPSE. Using stratified method, 15 soil samples were collected from each playground. Standard procedures were employed in the isolation of the fungal species; Atlas of mycology was used to identify the isolates based on their macro and micromorphologies. Pathogenic fungi isolated include Microsporum gypseum (16.13%), Microsporum canis (12.90%), Aspergillus flavus (6.45%), Aspergillus niger (9.68%), Aspergillus fumigatus (6.45%), Rhizopus stolonifer (6.45%), Fusarium sp. (6.45%), Trichophyton rubrum (9.68%), Trichophyton mentagrophytes (9.68%), Penicillium sp. (9.68%), and Alternaria sp. (9.68%). Microsporum gypseum was isolated from all the five schools. The presence of these pathogenic fungi from all the study sites heightens public health concern.